Keanekaragaman Tumbuhan Berpotensi Sebagai Tanaman Hias Di Aek Nauli, Sumatera Utara - Faisal, Muhammad; Ananda, Uci Fitri; Balqis, Zia Syamsia; Fadhila, Puan; Syahputri, Nidy (CV. ITTC INDONESIA, 2024)
Abstract This study aims to identify various types of plants that have the potential as ornamental plants found in the Aek Nauli Forest, North Sumatra. Ornamental plants, as part of horticulture, have a wide diversity of types and have the potential to make a significant contribution to improving the economy. This study was conducted using an exploration survey method, namely through direct observation at the research location. The data collection technique used an exploration method to reach various areas that are plant habitats. The results of the analysis of this survey showed that there were seven types of ornamental plants found in the Aek Nauli Forest area, namely Melastoma sanguinea, Coelogyne brachygyne, Homalomena rubescens, Pandanus sp., Hydrangea macrophylla, Euphorbia pulcherrima, and Spathoglottis plicata. The diversity of ornamental plant types reflects the great potential of the Aek Nauli Forest as a floral resource with economic and aesthetic value.